Dynamic Bonds Reinforced Polyamide Elastomer for Biomedical Orthosis - Zhen Li; Peiyao Yan; Hao Wang; Yuancheng Zhang; Junhua Kong; Wei Zhao; Xin Li; Xiaomeng Zhang; Zhe Cui; Peng Fu; Xinchang Pang; Minying Liu; et al. (Advanced Science)
Abstract 4D printing of shape memory polymers (SMPs) allows the 3D‐printed structures to have adjustable shapes, properties, and functionalities, paving the way for intelligent devices and multifunctional applications. However, 4D‐printed SMPs face challenges due to mechanical anisotropy and mediocre shape memory performance hampered by weak interlayer adhesion. This study innovatively integrates shape memory polyamide elastomer with 4D printing technology to develop a multifunctional intelligent orthosis. Here, a dynamic bonds (DBs) reinforced shape memory polyamide elastomer is developed using a twin‐screw extruder through reactive extrusion. Dynamic covalent networks are introduced into polyamide elastomer, which enhances interlayer adhesion in 4D‐printed objects by utilizing combined effects of multiple dynamic covalent bonds (DCBs) and hierarchical hydrogen bonds (DHBs), leading to the reduction of mechanical anisotropy and improvement of the mechanical and shape memory properties of the 4D printouts. 4D‐printed objects demonstrated excellent macroscopic shape memory and reconfiguration, showcasing the versatility of this material, and the application for spinal orthosis is also demonstrated.